ECONOMIC MODERNIZATION AND SUSTAINABLE DEVELOPMENT - Madina Norbutaeva Raxmatullo qizi (Web of Journals Publishing, 2024)
This article delves into the intersection of economic modernization and sustainable development, examining how countries can achieve both economic growth and environmental sustainability. It explores existing literature to understand the challenges, opportunities, and potential strategies for bridging the gap between economic advancement and sustainable practices. Through a comprehensive analysis, this article aims to provide insights into the methods, results, and implications of pursuing a path of sustainable economic development.
Keywords: Economic modernization, sustainable development, growth, environmental sustainability, social equity, innovation, policy frameworks.